Energy scaling in a compact bulk multi-pass cell enabled by Laguerre–Gaussian single-vortex beams - V. Koltalo; S. Westerberg; M. Redon; G. Beaufort; A.-K. Raab; C. Guo; C. L. Arnold; A.-L. Viotti (APL Photonics)
We report pulse energy scaling enabled by the use of Laguerre–Gaussian single-vortex (LG0,l) beams for spectral broadening in a sub-40 cm long Herriott-type bulk multi-pass cell. Beams with orders l = 1–3 are generated using a spatial light modulator, facilitating rapid and precise reconfiguration of the experimental conditions. 180 fs pulses with 610 μJ pulse energy are post-compressed to 44 fs using an LG0,3 beam, boosting the peak power of an ytterbium laser system from 2.5 GW to 9.1 GW. The spatial homogeneity of the output LG0,l beams is quantified, and the topological charge is spectrally-resolved and is shown to be conserved after compression by employing a custom spatiotemporal coupling measurement setup.